STRATEGI PENGEMBANGAN AGRIBISNIS KEDELAI LOKAL UNTUK MENINGKATKAN PENDAPATAN PETANI DI KABUPATEN LOMBOK TENGAH - Mohammad Rizky Ridhanto; Muhlisin Muhlisin; Ayuningtyas Nilasari (MEDIAGRO, 2020)
West Nusa Tenggara is one of the major soybean producing regions in Indonesia. The largest contribution to the province's soybean production comes from Central Lombok Regency. In the last three years, the average production of Central Lombok Regency was 28,314 tons. Developments that occurred in the last three years showed a decrease every year. Soybean agribusiness potential in Central Lombok Regency has a large prospect with the need to increase every year, the need for greater soybean seed needs. But with production declining every year, the development of soybean agribusiness in the district is not going well. This research is aimed at analyzing local soybean development strategies and formulating appropriate strategies applied in Central Lombok Regency. This research method is a descriptive qualitative research. While the analysis method used is the Internal Factor Evaluation - External Factor Evaluation (IFE-EFE) matrix, SWOT, and the Quantitative Strategic Planning Matrix (QSPM). The analysis in this research results in developing strategies, developing markets and developing products that are appropriate for the development of local soybean agribusiness. The priority strategy that can be developed in Central Lombok is the development of agricultural area systems so that the agribusiness system can be implemented from sub-systems such as the system to the marketing of products. Keywords: soybean, strategy, IFE-EFE, SWOT, QSPM.